2024
DOI: 10.1051/shsconf/202418201011
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Personalised Learning to Teach English in Malaysian Low-Enrolment Schools

Noorfatin Zakaria,
Geoffrey F.C. Lim,
Norshamshizar Abdul Jalil
et al.

Abstract: The implementation of personalised learning in teaching English has become one of the effective approaches to cater learners’ needs in education. The educators in Malaysia, as in many countries, are interested in exploring the implementation of personalised learning in their lessons. However, the study on personalised learning to teach English in Malaysian schools is scarce. The prevalence of low academic achievement, especially in rural and low-enrolment schools, has led to teacher reluctance to adopt persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…These rural areas were primarily marked by unfavorable conditions, such as economic constraints, cultural limitations, and challenges in transportation. Families in these rural areas generally exhibited a lower socioeconomic status, and schools were often situated in remote regions where access to information technology and educational opportunities was comparatively insufficient compared to urban schools (Zakaria et al, 2024). Karal et al (2011) identified key factors influencing students' perceptions of synchronous distance education: technological issues, instructors, environment, curriculum, and distance.…”
mentioning
confidence: 99%
“…These rural areas were primarily marked by unfavorable conditions, such as economic constraints, cultural limitations, and challenges in transportation. Families in these rural areas generally exhibited a lower socioeconomic status, and schools were often situated in remote regions where access to information technology and educational opportunities was comparatively insufficient compared to urban schools (Zakaria et al, 2024). Karal et al (2011) identified key factors influencing students' perceptions of synchronous distance education: technological issues, instructors, environment, curriculum, and distance.…”
mentioning
confidence: 99%